Use of a Brief Screening Tool to Assess Intellectual Functioning in a Forensic Population - Donohue, Andrew; Samuels, Jack; Thompson, Robert; Watson, Clarence; Gallucci, Gerard (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Individuals with intellectual disability are over-represented in forensic settings, including jails, prisons and forensic psychiatric treatment units. Identification of intellectual disability is important in such settings, especially in light of the implications of intellectual disability in legal issues including competency to stand trial, criminal responsibility and capital sentencing. We examined the utility of a brief test of intelligence (PROFOKS), assessing knowledge of proverbs, fund of knowledge and similarities in a series of 29 inpatients residing in a forensic psychiatric unit. PROFOKS correlated strongly with performance on the Wechsler Abbreviated Scale of Intelligence (WASI), including the full scale, verbal and performance IQs and WASI subscales. The PROFOKS appears to be a useful screening tool in identifying intellectual disability in a forensic psychiatric population.